2022
DOI: 10.1002/jmri.28076
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four‐Dimensional Magnetic Resonance Imaging Analysis of Left Ventricular Fluid Dynamics and Energetics in Ischemic and Restrictive Cardiomyopathies

Abstract: Background Time‐resolved three‐directional velocity‐encoded (4D flow) magnetic resonance imaging (MRI) enables the quantification of left ventricular (LV) intracavitary fluid dynamics and energetics, providing mechanistic insight into LV dysfunctions. Before becoming a support to diagnosis and patient stratification, this analysis should prove capable of discriminating between clearly different LV derangements. Purpose To investigate the potential of 4D flow in identifying fluid dynamic and energetics derangem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Of note, an earlier study by Garg et al (32) found that MI patients with preserved systolic function also had reduced peak E wave (early) diastolic KE -early evidence of the diastolic dysfunction that can occur post MI. A significant reduction in peak E wave KE was also observed in patients with cardiac amyloidosis (35), a condition characterized by diastolic dysfunction and heart failure with preserved ejection fraction.…”
Section: Left Ventricular Diastolic Kinetic Energymentioning
confidence: 80%
“…Of note, an earlier study by Garg et al (32) found that MI patients with preserved systolic function also had reduced peak E wave (early) diastolic KE -early evidence of the diastolic dysfunction that can occur post MI. A significant reduction in peak E wave KE was also observed in patients with cardiac amyloidosis (35), a condition characterized by diastolic dysfunction and heart failure with preserved ejection fraction.…”
Section: Left Ventricular Diastolic Kinetic Energymentioning
confidence: 80%
“…Recent years have witnessed rapid advancements in imaging technology and methods of image analysis that provide deeper informative content regarding cardiac function. By first principles, heart function is about creating and sustaining blood motion; therefore, placing the focus on measures associated with blood flow promises further progress along this line 1 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The study of the flow transit is an important step for the evaluation of blood transport and mixing inside the LV, this is useful for the identification of the blood residences and wash-out properties; conditions that are related to the risk of the thrombus formation. Following the established literature in cardiology 22 , 23 , 45 , this evaluation is obtained through the subdivision of EDV in four sub-volumes where (also indicated as ) is the volume of blood that entered during diastole and transits directly to the aortic outlet during systole, thus residing less than one heartbeat in the LV. is the quantity of blood already present in the LV at the beginning of diastole and ejected during the following systole.…”
Section: Methodsmentioning
confidence: 99%
“…In the CMR field, new techniques may also bring more insights on diagnosis and pathophysiology of amyloidosis in a near future. Four‐dimensional magnetic resonance imaging showed derangements in left ventricular diastolic fluid dynamics in patients with AL CA 89 . Diffusion tensor cardiovascular magnetic resonance demonstrated elevated mean diffusivity and reduced fractional anisotropy in CA, depicting the microstructural effects of amyloid infiltration and identifying the extent of the expanded disorganized myocardium.…”
Section: Future Directionsmentioning
confidence: 98%
“…Fourdimensional magnetic resonance imaging showed derangements in left ventricular diastolic fluid dynamics in patients with AL CA. 89 Diffusion tensor cardiovascular magnetic resonance demonstrated elevated mean diffusivity and reduced fractional anisotropy in CA, depicting the microstructural effects of amyloid infiltration and identifying the extent of the expanded disorganized myocardium. Diffusion tensor parameters were found to be linked to extracellular amyloid deposition assessed by ECV.…”
Section: Future Directionsmentioning
confidence: 98%